Swiss Orthopaedics Minimal Dataset: First Pilot Report of Reliability and Validity - Thorsten Jentzsch; Claudio Dora; Urs Müller; Mazda Farshad (Advances in Orthopedics)
Background. The Swiss Orthopaedics Minimal Dataset (SOMD) was launched seven years ago. It is a standardized, generic, and patient-reported outcome questionnaire, comprising ten items (location of disease, pain within the past four weeks, limitations at work/leisure/sleep/autonomy, subjective value of a body part, employment status, work disability (sick leave/pension), and household support). We conducted this study about the SOMD to report its reliability, validity, and clinical applicability. Methods. A retrospective observational cohort study was conducted. The test-retest study population (n = 60; lost to follow-up: n = 7 (12%)) was drawn from three retirement homes (in 2013), while the test study population (n = 14,180; excluded (e.g., duplicates): n = 1,990 (14%)) consisted of patients from a university hospital (in 2014–2017). In the test-retest study population, the same questionnaire was completed twice (at days 0 and 7). In the test study population, only the first questionnaire was included (to avoid duplicates). In a subgroup of the test study population (n = 302), only those patients who completed the SOMD and Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) of the hip within 14 days were considered (to minimize recall bias). Reliability (test-retest and internal consistency), criterion validity for the item of pain, and return rates were analyzed. Results. The test-retest study population (n = 53) showed very high test-retest reliability for all tested items of the SOMD (intraclass correlation coefficient = 0.96–1.00 (95% confidence interval 0.93–1.00), p<0.001). The test study population (n = 12,190) revealed good internal consistency reliability for all ten items (Cronbach’s alpha = 0.80). The return rates of the SOMD were improvable (43% in 2016 and 31% in 2017). The subgroup of the test study population (n = 302) displayed a borderline acceptable criterion validity (correlation of the item of pain between SOMD and WOMAC hip: rho = 0.62, p<0.001). Conclusion. This is the first report about the validation of the SOMD. A relatively high reliability (test-retest and internal consistency), borderline acceptable (criterion) validity for the item of pain, and improvable clinical implementation were observed. This analysis serves as the basis for a structured modification of the SOMD to improve its value.